Atividade das enzimas arilsulfatase e betaglicosidase em diferentes ambientes de produção e sua relação com atributos físico-químicos do solo na região noroeste do Rio Grande do Sul - Desconsi, Maicon (2024)
The sustainable increase in crop productivity is closely linked to soil quality. Therefore, it is necessary to use tools for analyzing physical, chemical and biological indicators, capable of determining the current situation of the soil, its resilience and assisting in the decision-making process, promoting the maintenance of the productive sustainability of environments. The enzymatic activity of arylsulfatase and beta-glucosidase are used as biological indicators of soil quality in several studies, being able to point out in advance the changes that occur due to their use and management, as they have a direct effect on soil processes and sensitivity greater to physical and chemical indicators. Beta-glucosidase acts in the final part of the cellulose decomposition process, hydrolyzing cellobiose fragments into glucose molecules. Arylsulfatase comprises a group of enzymes that mineralize organic sulfur to SO42-. The present study aimed to evaluate the enzymatic activity of beta-glucosidase and arylsulfatase in soybean crops in the Northwest of the State of Rio Grande do Sul and its interaction with the physical-chemical attributes of the soil. A total of 379 soil analyzes of 28 producers were examined. The analyzed areas were defined in zones of high, medium and low productive potential. All samples were subjected to chemical analysis of granulometry, macro and micronutrients. The data were subjected to a descriptive statistical analysis, using the statistical package SAS (Statistical Analysis Systems), where the correlation between enzymatic activity with different soil attributes was determined. Beta-glucosidase and arylsulfatase activities showed a positive correlation with OM, pH, CTC and base saturation levels, and a negative correlation with aluminum saturation. The enzymatic activity of beta-glucosidase and arylsulfatase showed an important correlation with fundamental attributes of soil fertility, reinforcing the use of these parameters as soil quality bioindicators. Only beta-glucosidase was able to distinguish low productive potential areas, of medium and high potential areas, in the Northwest region of the State of Rio Grande do Sul.